Cultural Policy in the Digital Age: The Emergence of Fans as Political Agents in Copyright Discourse - Beauregard, Devin (Université d'Ottawa / University of Ottawa, 2011)
Cultural policy theory operates on a division between producers and the public. Dualisms, such as producer/consumer – or, in more nuanced circles, the triadic relationship of consumer/producer/owner – have had a structuring effect on the way in which we envision cultural policy theories. At its core, the producer/consumer dualism implies subjectivities – that is to say that it defines positions in relationships between socio-political actors/actresses. At the governmental level, such clear-cut subject positions are perceptible beyond theories, entering into the actual practice of policy-making to the point where certain policies structure the notion of the public (or consumers), and the producers and/or owners. Copyright law, for instance, represents a good example of such an ideational construct. As a form of cultural policy, copyright law seeks to define the rights of producers with regards to their productions. Consequently, this thesis aims at exploring the forms of agency that develop and challenge both the practice and theoretical constructs of cultural policy. Two aspects command us to question anew these boundaries, one based on contemporary social and technical transformations (the rise of the digital age), and one based on cultural practice (in this case, those of fans and fandoms).Borrowing from theories of cultural studies and Foucauldian approaches to discourse analysis, this thesis explored the emerging discourses surrounding fans and their use of copyrighted material via the internet. Putting emphasis on three fandoms that have had marked histories of fan activism and fan production via the use of copyrighted material – Star Trek, Firefly, and Harry Potter – this paper investigated fans’ use of copyrighted material in developing fan cultures and as a vehicle for their discursive practices. These cases illustrate how fans have challenged the established repertoires of subjects in cultural policy (making and theory), and how their form of agency represents an interesting case of resistance to the rise of the cultural industries conception of cultural policy.
Keywords: cultural policy; copyright; fan labour; fans; cultural industries